Dominant TNFα and impaired IL‐2 cytokine profiles of CD4+ T cells from children with type‐1 diabetes. Issue 7 (25th April 2017) - Seyfarth, Julia; Förtsch, Katharina; Ahlert, Heinz; Laws, Hans‐Juergen; Karges, Beate; Deenen, Rene; Köhrer, Karl; Mayatepek, Ertan; Meissner, Thomas; Jacobsen, Marc
Abstract : Aberrantly activated CD4 + T memory cells play a central role in the development of type‐1‐diabetes. Interleukin‐7 promotes generation of autoimmune memory T cells and increased Interleukin‐7 availability is associated with type‐1‐diabetes susceptibility. T‐cell‐mediated immune pathology at onset of type‐1‐diabetes is well defined, but characteristics of long‐term symptomatic disease stages remain largely elusive. In the present study, memory CD4 + T‐cell activation and cytokine expression as well as sensitivity to Interleukin‐7 in vitro were compared between patients with type‐1‐diabetes at clinical onset ( n =25), long‐term symptomatic disease (median duration 4.5 years, n =19) and matched healthy controls ( n =21). T‐cell responses of type‐1‐diabetes patients were characterized by higher frequencies of cytokine and activation marker expressing CD4 + memory T cells as compared to healthy controls. Notably, correction for individual cytokine expression levels revealed qualitative differences of cytokine profiles characterized by significantly increased TNFα and decreased IL‐2‐expressing T‐cell proportions in long‐term type‐1‐diabetes patients. IL‐7‐mediated T‐cell co‐stimulation induced quantitative and qualitative cytokine expression differences highly similar to type‐1‐diabetes‐specific profiles. In addition, CD4 + memory T cells from children with long‐term type‐1‐diabetes were more sensitive to in vitro IL‐7 co‐stimulation. Global transcriptome analysis revealed IL‐7 induced expression differences of CD4 + T cells, including increased IL‐2R expression and effects on subsequent T‐cell receptor activation. We conclude that long‐term symptomatic type‐1‐diabetes patients differed in memory T‐cell cytokine profiles and Interleukin‐7 co‐stimulation. Regulation of IL‐2 expression and sensitivity are affected with possible consequences for disease course and severity at long‐term type‐1‐diabetes stages.